In vitro digestion characteristics of various combinations of elephant grass hay, gliricidia hay or silage, soybean meal and corn meal in rations for sheep - Juliana Caroline Santos Santana; Jucileia Aparecida da Silva Morais; Gelson dos Santos Difante; Luís Carlos Vinhas Ítavo; Antonio Leandro Chaves Gurgel; Vinicius da Silva Oliveira; Maria Juciara Silva Teles Rodrigues (Tropical Grasslands-Forrajes Tropicales, 2020)
This study examined fermentation rates and kinetics of sheep rations based on combinations of elephant grass hay, gliricidia (Gliricidia sepium) hay or silage, soybean meal and corn meal using in vitro techniques. Three rations were prepared, namely: Control (elephant grass hay + soybean meal + corn meal); gliricidia hay (elephant grass hay + soybean meal + corn meal + gliricidia hay); and gliricidia silage (elephant grass hay + soybean meal + corn meal + gliricidia silage). A fixed ratio of roughage:concentrate of 55:45 was maintained for all rations, which were isocaloric and designed to support sheep gains of 200 g/day. The gliricidia replaced 57.6% of the soybean meal in the rations containing gliricidia and 81.8% of the elephant grass hay. Fermentation rates and kinetics, in vitro dry matter digestibility (IVDMD) and degradability of the rations were evaluated. Rations containing gliricidia as both hay and silage had higher (P<0.05) IVDMD than the Control ration (67.8 and 66.2 vs. 59.8%). The degradability of the ration containing gliricidia hay was higher (P<0.05) than that of the gliricidia silage ration (57.8 vs. 50.5%), whereas the Control showed an intermediate value (54.4%). The ration containing gliricidia hay and the Control produced more gas in the first 24 h than the ration containing gliricidia silage, and the gliricidia hay ration showed the shortest colonization time. Peak gas production occurred for the ration with gliricidia silage later than for the other rations. The study showed that substituting soybean meal with preserved gliricidia can result in higher digestibility of sheep rations. Feeding studies with animals are now warranted to verify these laboratory findings.